Estimation of adaptability parameters of collection hulled oats varieties according to productivity in the Kirov region - M. V. Tulyakova; G. A. Batalova; S. S. Saltykov; S. V. Permyakova (Зерновое хозяйство России, 2024)
The current paper has presented the study results conducted on the experimental plot of the Falenskaya breeding station of the branch of the FSBI FANC of the North-East in 2021–2023.   The purpose of the study was to evaluate the collection hulled oat varieties according to grain productivity and adaptability parameters in the soil and climatic conditions of the Kirov region.   The materials for the study were 9 collection oat varieties and the standard variety ‘Krechet’. According to the trait ‘productivity’, there have been estimated adaptability parameters. During the testing years, the studied variety samples differed significantly in productivity variability (V = 16.8–30.0 %). The factor ‘year’ had the greatest effect on the formation of oat yields (90.3 %). In the arid year of 2021, the varieties’ productivity was low (276–401 g/m2), with a negative index of environmental conditions (Ij = -163), in the most favorable year of 2022, it was 463–682 g/m2 and Ij = 104, respectively. The variety samples ‘k-3967 0144’ (-190 g/m2) and ‘15584 Mutant 258’ (-214 g/m2) were characterized by high stress resistance. High genetic flexibility of mean productivity under contrasting conditions was established in the variety samples ‘15472 Sumphony’ (504 g/m2), ‘k-3967 0144’ (496 g/m2) and ‘15340 Uran’ (487 g/m2). There have been identified such gene sources as plastic ‘k-3967 0144’, ‘15472 Sumphony’, ‘15340 Uran’, ‘k-3951 0146’, ‘k-3954 0149’ (IEP = 1.13–1.0), and with high stability of the trait ‘productivity’ ‘k-3967 0144’, ‘15584 Mutant 258’, ‘k-3954 0149’ (SF = 1.47–1.78). Low variability and high homeostaticity were found in the variety samples ‘k-3967 0144’, ‘15584 Mutant 258’, ‘k-3954 0149’ (V = 16.8–22.8 %; Hom = 31.31–20.75) with a high stability index (Is = 5.95–4.38). The adaptability coefficient has confirmed the high adaptability of variety samples ‘k-3967 0144’, ‘15472 Sumphony’ and ‘15340 Uran’ (KA =112.3–108 %). In adaptive breeding for further work, the varieties ‘k-3967 0144’, ‘15584 Mutant 258’, ‘k-3954 0149’, ‘15472 Sumphony’, ‘15340 Uran’ are of great interest, since they are the most adaptive in terms of the sum of ranks. Based on a comprehensive estimation of productivity and adaptability parameters, ‘k-3967 0144’ was recognized as the best variety sample, which can give a large mean productivity (526 g/m2) in changing weather conditions.